2020
DOI: 10.1162/jocn_a_01436
|View full text |Cite
|
Sign up to set email alerts
|

The Common Rhythm of Action and Perception

Abstract: Research in the last decade has undermined the idea of perception as a continuous process, providing strong empirical support for its rhythmic modulation. More recently, it has been revealed that the ongoing motor processes influence the rhythmic sampling of sensory information. In this review, we will focus on a growing body of evidence suggesting that oscillation-based mechanisms may structure the dynamic interplay between the motor and sensory system and provide a unified temporal frame for their effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 151 publications
5
45
0
Order By: Relevance
“…Recent research has demonstrated the presence of visual oscillations synchronized with action onset (Benedetto et al, 2018;Benedetto et al, 2019;Benedetto & Morrone, 2017;Hogendoorn, 2016;Tomassini et al, 2017;Tomassini et al, 2015;Wutz et al, 2016;Zhang et al, 2019). In particular, delta oscillations in visual sensitivity have been shown in contrast discrimination between highly salient stimuli (Benedetto & Morrone, 2017;Hogendoorn, 2016), phase-locked to saccadic events, likely reflecting a synchronization between endogenous visual neuronal rhythms and the oculomotor system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has demonstrated the presence of visual oscillations synchronized with action onset (Benedetto et al, 2018;Benedetto et al, 2019;Benedetto & Morrone, 2017;Hogendoorn, 2016;Tomassini et al, 2017;Tomassini et al, 2015;Wutz et al, 2016;Zhang et al, 2019). In particular, delta oscillations in visual sensitivity have been shown in contrast discrimination between highly salient stimuli (Benedetto & Morrone, 2017;Hogendoorn, 2016), phase-locked to saccadic events, likely reflecting a synchronization between endogenous visual neuronal rhythms and the oculomotor system.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the hypothesis of a strong link between sensorimotor integration and neural oscillations, it has been demonstrated that the phase of neural oscillations can predict reaction-time to perceptual events (Drewes & VanRullen, 2011;Lansing, 1957;Surwillo, 1961), and that a transient visual response can reset the phase of low-frequency tremor oscillations in peripheral muscles (Wood, Gu, Corneil, Gribble, & Goodale, 2015). This link between motor and visual rhythmic activity has been reinforced by Tomassini, Ambrogioni, Medendorp, and Maris (2017) who demonstrated that EEG theta-band oscillatory activity, measured seconds before the action onset, predicts visual performance in an Citation: Benedetto, A., & Morrone, M. C. (2019). Visual sensitivity and bias oscillate phase-locked to saccadic eye movements.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The likely reason for this is that the brain's neuronal activity is inherently rhythmic, influencing both the generation of motor activity and the perception of sensory inputs (Buzsáki, 2006), which go hand in hand during active sensing. Previous studies (see (Benedetto et al, 2020) for a review), indicate that rhythmic motor sampling patterns are capable of adjusting neural excitability fluctuations in sensory brain regions to align with the rhythm of the motor production signals (Sperry, 1950). The alignment of rhythmic excitability fluctuations to some other, internal or external rhythmic process is termed neuronal entrainment.…”
Section: Introductionmentioning
confidence: 99%
“…Motor preparation and execution, such as finger tapping, button press, reaching or grasping actions and even isometric muscle contraction, can modulate the perception of visual stimuli (for a review see Benedetto et al, 2020). From hundreds of milliseconds before action onset (during motor preparation) to up to 1 second after action offset, visual sensitivity oscillates in synchrony with action onset at a frequency in the theta range (Benedetto et al, 2016;Tomassini et al, 2015;Zhang et al, 2019).…”
Section: Model Of the Bold Response Component Of The Visuo-motor Systemmentioning
confidence: 99%